THE IMPACT OF ELECTRONIC WORDOF MOUTH (e-WOM) ON HOTEL ROOM PURCHASE DECISIONS AT TRAVELOKA AT HOTEL PARKSIDE PETROGAYO HOTEL TAKENGON - Rizkan; Heriyana; T.Edyansyah; Hamdiah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the influence of Electronic Word of Mouth (e-WOM) on hotel room purchase decisions on Traveloka, especially at the Parkside Petro Gayo Takengon Hotel. The phenomenon of increasing internet and e-commerce users has changed consumer behavior, making online reviews and recommendations a crucial factor in hotel purchase decisions. The purpose of this study is to identify and analyze the positive and significant influence of e-WOM on hotel room purchase decisions on Traveloka at the Parkside Petro Gayo Takengon Hotel. Identifying e-WOM factors that influence purchase decisions, namely Intensity, Valence of Opinion, and Content. This study uses a quantitative approach by distributing questionnaires to 100 respondents, namely tourists who booked hotel rooms at Parkside Petro Gayo Takengon through Traveloka. Data were analyzed using validity tests, reliability tests, classical assumptions (normality, multicollinearity, heteroscedasticity), and multiple linear regression analysis. The results of the hypothesis test show that Intensity, Valence of Opinion, and Content positively and significantly influence hotel room purchase decisions on Traveloka at the Parkside Petro Gayo Takengon Hotel. The higher the intensity of information, the more positive the valence of opinion, and the better the information content, the more it increases consumer purchasing decisions.